Life histories and conservation of long‐lived reptiles, an illustration with the American crocodile (Crocodylus acutus). (31st July 2017) - Briggs‐Gonzalez, Venetia; Bonenfant, Christophe; Basille, Mathieu; Cherkiss, Michael; Beauchamp, Jeff; Mazzotti, Frank
Abstract: Successful species conservation is dependent on adequate estimates of population dynamics, but age‐specific demographics are generally lacking for many long‐lived iteroparous species such as large reptiles. Accurate demographic information allows estimation of population growth rate, as well as projection of future population sizes and quantitative analyses of fitness trade‐offs involved in the evolution of life‐history strategies. Here, a long‐term capture–recapture study was conducted from 1978 to 2014 on the American crocodile ( Crocodylus acutus ) in southern Florida. Over the study period, 7, 427 hatchlings were marked and 380 individuals were recaptured for as many as 25 years. We estimated survival to be strongly age dependent with hatchlings having the lowest survival rates (16%) but increasing to nearly 90% at adulthood based on mark–recapture models. More than 5% of the female population were predicted to be reproductive by age 8 years; the age‐specific proportion of reproductive females steadily increased until age 18 when more than 95% of females were predicted to be reproductive. Population growth rate, estimated from a Leslie–Lefkovitch stage‐class model, showed a positive annual growth rate of 4% over the study period. Using a prospective sensitivity analysis, we revealed that the adult stage, as expected, was the most critical stage for population growth rate; however, the survival of younger crocodiles before they became reproductive also had a surprisingly high elasticity. We found that variation in age‐specific fecundity has very limited impact on population growth rate in American crocodiles. We used a comparative approach to show that the original life‐history strategy of American crocodiles is actually shared by other large, long‐lived reptiles: while adult survival rates always have a large impact on population growth, this decreases with declining increasing growth rates, in favour of a higher elasticity of the juvenile stage. Crocodiles, as a long‐lived and highly fecund species, deviate from the usual association of life histories of "slow" species. Current management practices are focused on nests and hatchling survival; however, protection efforts that extend to juvenile crocodiles would be most effective for conservation of the species, especially in an ever‐developing landscape. Abstract : The authors provide evidence of unique life history for long‐lived reptiles, using an extensive, empirical dataset on American crocodiles to challenge the classic view of the slow–fast continuum, and calls for conservation action targeting juvenile stages.